Male description and intraspecific variations of Cyrtopsis t-sigillata (Orthoptera: Tettigoniidae: Meconematinae) - Song, Qiong; Du, Bao-Jie; Shi, Fu-Ming (Zootaxa, 2015)
The paper describes the male of Cyrtopsis t-sigillata Liu, Zhou & Bi, 2010 for the first time, and discusses individual variations in the species. It provides the photos of important morphological features, and offers a distribution map about the genus Cyrtopsis Bey-Bienko, 1962. The examined material is deposited in the Museum of Hebei University. Morphological images were acquired using Leica M205 A digital imaging system.